2016
DOI: 10.1111/eje.12239
|View full text |Cite
|
Sign up to set email alerts
|

Exploring uses of the UK Clinical Aptitude Test‐situational judgement test in a dental student selection process

Abstract: This study has shown that the UKCAT SJT does not add value to the existing methods of this dental school to make valid, reliable and fair student selection decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…Three authors reported a negative correlation between the method of selection and their outcome measure. 28,31,58 A moderate correlation between selection test and dental school assessment was found by four authors in relation to the UKCAT, 28 previous academic scores, 5 a non-structured interview 55…”
Section: Selection Tool Used and Predictive Validitymentioning
confidence: 95%
See 3 more Smart Citations
“…Three authors reported a negative correlation between the method of selection and their outcome measure. 28,31,58 A moderate correlation between selection test and dental school assessment was found by four authors in relation to the UKCAT, 28 previous academic scores, 5 a non-structured interview 55…”
Section: Selection Tool Used and Predictive Validitymentioning
confidence: 95%
“…However, in most cases, the strength of relationship (r), evaluated using Cohen's conventions 68 (0.10 weak, 0.30 moderate, 0.5 strong), was a weak correlation between only part of the selection test or outcome measure (n = 9). 5,29,30,55,56,[59][60][61]67 In some cases, correlations were reported between a section of an admission test, 5,29,30,61,64,65 such as a single interview question, and/or small sections of the outcome measure, 28,30,31,54,55 such as a single examination result. Three authors reported a negative correlation between the method of selection and their outcome measure.…”
Section: Selection Tool Used and Predictive Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, authors should always cite evaluation evidence of the selection method in question, as opposed to, for example, suggesting an admissions interview is valid simply because it is structured (see a recent paper by Lambe and colleagues). 14…”
Section: The Research Problemmentioning
confidence: 99%